2021
DOI: 10.1017/ice.2021.400
|View full text |Cite
|
Sign up to set email alerts
|

Postdischarge prophylactic antibiotics following mastectomy with and without breast reconstruction

Abstract: Background: Prophylactic antibiotics are commonly prescribed at discharge for mastectomy, despite guidelines recommending against this practice. We investigated factors associated with postdischarge prophylactic antibiotic use after mastectomy with and without immediate reconstruction and the impact on surgical-site infection (SSI). Study design: We studied a cohort of women aged 18–64 years undergoing mastectomy between January 1, 2010, and June 30, 2015, using the MarketScan commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…[14][15][16][17] Claims and insurance database studies including large numbers of patients have shown limited benefit (number needed to treat, 48) or no benefit at all. 4,18,19 These data have been reflected in more recent meta-analyses that have supported discontinuation of EAP use. 20,21 Despite these findings, the use of oral antibiotic prophylaxis beyond 24 hours after surgery has remained a mainstay of infection prevention efforts for plastic surgeons.…”
Section: Ementioning
confidence: 90%
See 1 more Smart Citation
“…[14][15][16][17] Claims and insurance database studies including large numbers of patients have shown limited benefit (number needed to treat, 48) or no benefit at all. 4,18,19 These data have been reflected in more recent meta-analyses that have supported discontinuation of EAP use. 20,21 Despite these findings, the use of oral antibiotic prophylaxis beyond 24 hours after surgery has remained a mainstay of infection prevention efforts for plastic surgeons.…”
Section: Ementioning
confidence: 90%
“…14–17 Claims and insurance database studies including large numbers of patients have shown limited benefit (number needed to treat, 48) or no benefit at all. 4,18,19 These data have been reflected in more recent meta-analyses that have supported discontinuation of EAP use. 20,21…”
mentioning
confidence: 90%